2021
DOI: 10.1002/macp.202100326
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Technologies for Obtaining Desired Stiffness Gradients in GelMA Hydrogels Constructs

Abstract: This work presents enabling technologies for the optimization of the manufacturing of GelMA‐based hydrogels constructs with desired stiffness gradients. The manufacturing technique combines dynamic mixing for gradient generation and a passive micromixer for efficient hydrogel blending. A digital replica of the fabrication process is developed, integrating theoretical and computational models, as well as experimental data, in order to predict and control the stiffness profile obtained within the constructs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For the preparation of hydrogels, various types of polymers, from natural to synthetic, have been used. Although natural polymers are generally preferred because of their similarity to the ECM structure, biocompatible nature, and rich protein content, synthetic polymers have often been chosen because of their adjustable mechanical and degradable properties, easy production process, and nonimmunogenic nature. , In addition, parameters such as viscoelastic property, structural integrity, stability, and degradation behavior of the developed gels should be taken into account for the formation of spheroids. , …”
Section: Conventional 3d Cell Culture Techniques Used For Spheroid En...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the preparation of hydrogels, various types of polymers, from natural to synthetic, have been used. Although natural polymers are generally preferred because of their similarity to the ECM structure, biocompatible nature, and rich protein content, synthetic polymers have often been chosen because of their adjustable mechanical and degradable properties, easy production process, and nonimmunogenic nature. , In addition, parameters such as viscoelastic property, structural integrity, stability, and degradation behavior of the developed gels should be taken into account for the formation of spheroids. , …”
Section: Conventional 3d Cell Culture Techniques Used For Spheroid En...mentioning
confidence: 99%
“…49,50 In addition, parameters such as viscoelastic property, structural integrity, stability, and degradation behavior of the developed gels should be taken into account for the formation of spheroids. 51,52 Ultimately, the labor-intensive and time-consuming nature of these 3D conventional culture techniques, in addition to the difficulty of changing the culture medium, the low-yield production, the difficulty of controlling the spheroid size, and cross-contamination issues, have prompted researchers to investigate microfluidic approaches for spheroid production. 53,54…”
Section: Conventional 3d Cell Culture Techniques Used For Spheroid En...mentioning
confidence: 99%
“…GelMA hydrogels can be synthesized with a specific degree of functionalization (DoF) and tailored to the intended application as a three-dimensional (3D) cell-culture platform. Piao et al discovered that significantly higher pressure was needed to dispense cell-laden GelMa from glass capillary, but that cell vitality and proliferates weren’t significantly impacted [ 64 , 65 ].…”
Section: 3d Bioprinting Techniquesmentioning
confidence: 99%
“…GelMA is a semi-synthetic hydrogel consisting of gelatin derivatized with methacrylamide and methacrylate groups. Sauty et al (2022). experimented that GelMA hydrogels can be synthesized with a specific Degree of Functionalization (DoF) and adjusted to the intended application as a three-Dimensional (3D) cell culture platform and GelMa was also shown to support cartilage tissue formation using chondrocytes and MSCs (Sauty et al, 2022).…”
Section: Gelatin-methacryloyl (Gelma)mentioning
confidence: 99%
“…Sauty et al (2022). experimented that GelMA hydrogels can be synthesized with a specific Degree of Functionalization (DoF) and adjusted to the intended application as a three-Dimensional (3D) cell culture platform and GelMa was also shown to support cartilage tissue formation using chondrocytes and MSCs (Sauty et al, 2022). Piao et al (2021) found out that while dispensing cell-laden GelMa from a glass capillary significantly higher pressure was required; however, cell vitality and proliferation weren't significantly affected.…”
Section: Gelatin-methacryloyl (Gelma)mentioning
confidence: 99%